Cultured Meat in Islamic Perspective - Hamdan, Mohammad Naqib; Post, Mark J.; Ramli, Mohd Anuar; Mustafa, Amin Rukaini (Springer, 2018)
Cultured meat is a promising product that is derived through biotechnology that partially circumvents animal physiology, thereby being potentially more sustainable, environmentally friendly and animal friendly than traditional livestock meat. Such a novel technology that can impact many consumers evokes ethical, philosophical and religious discussions. For the Islamic community, the crucial question is whether cultured meat is halal, meaning compliant with Islamic laws. Since the culturing of meat is a new discovery, invention and innovation by scientists that has never been discussed by classical jurists (fuqaha’), an ijtihad by contemporary jurists must look for and provide answers for every technology introduced, whether it comply the requirements of Islamic law or not. So, this article will discuss an Islamic perspective on cultured meat based on the original scripture in the Qur’an and interpretations by authoritative Islamic jurists. The halal status of cultured meat can be resolve through identifying the source cell and culture medium used in culturing the meat. The halal cultured meat can be obtained if the stem cell is extracted from a (Halal) slaughtered animal, and no blood or serum is used in the process. The impact of this innovation will give positive results in the environmental and sustain the livestock industry.